Nitric oxide and sensory nerves are involved in the vasodilator response to acetylcholine but not calcitonin gene-related peptide in rat skin microvasculature. - Ralevic, V. (1992)
1. The contributions of sensory nerves and nitric oxide (NO) to vasodilator responses to acetylcholine (ACh) and calcitonin gene-related peptide (CGRP) were examined in rat skin microvasculature with a laser Doppler flowmeter to monitor relative blood flow. 2. Perfusion of ACh (100 microM; for 30 min) over a blister base on the rat hind footpad elicited microvascular vasodilatation and this response was not sustained. CGRP (1 microM; 10 min perfusion) also elicited vasodilatation and this response was maintained even when CGRP was no longer in contact with the blister base. 3. The vasodilator response to ACh was significantly smaller in rats pretreated as neonates with capsaicin to destroy primary sensory afferents than it was in age-matched controls. The vasodilator response to CGRP was unaffected by capsaicin pretreatment. 4. Selective inhibitors of NO synthase, NG-nitro-L-arginine (L-NOARG) and NG-monomethyl-L-arginine (L-NMMA) (both at 100 microM) attenuated the vasodilator response to ACh in control rats, but had no effect on the vasodilator response to CGRP. There was a significant L-NOARG-resistant component in control rats while in capsaicin-treated rats the vasodilator response to ACh was virtually abolished by L-NOARG. The inactive stereoisomer NG-monomethyl-D-arginine (100 microM) did not affect the vasodilator response to ACh. 5. The efficacy of L-NOARG and L-NMMA as inhibitors of endothelium-dependent responses was confirmed by use of an endothelium-dependent vasodilator, the calcium ionophore A23187 (100 microM; 10 min perfusion). Vasodilatation to A23187 was strongly attenuated by both L-NOARG and L-NMMA.(ABSTRACT TRUNCATED AT 250 WORDS)